EVALUATION OF THE EFFICACY AND SAFETY OF ORAL PREGABALIN ON REDUCTIONOFPOST LICHTENSTEIN HERNIORRHAPHYINTRAVENOUS OPIOID CONSUMPTION, IN COMPARISON WITH CONTROL GROUP ZANJAN AYATOLLAH MOUSAVI HOSPITAL 2014/2015I - N., Salehi1, . Moghimi2, M.; V, Salehi1,* (university of eloued جامعة الوادي, 2018)
Pregabalinlowered opioid consumption. With regard to adverse effects those are limited to first 12 h after surgery pregabalin can be suggested for pain relief but its usage in elderly patients should be warily.
artical
Keywords: Pregabalin, inguinal hernia, Pethidine